Radiation-stimulated processes in silicon structures with contacts based on TiN - Nasyrov, M.U.; Ataubaeva, A.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The influence of irradiation on the structural properties of titanium nitride films deposited on silicon wafers has been considered. It has been shown that depending on the energy, fluence and type of irradiation ion, observed are the increase of accumulated damages with decreasing the grain size, the grain size reduction with increasing the fluence, the increase of dislocation density and microstrains.